Green skills and environmental awareness in vocational education and training : synthesis report - (:unkn) unknown (Publications Office of the European Union, 2012)
"The greening of the European economy, as outlined in the EU 2020 strategy, will have profound effects on the labour market and the development of the skills of the European population. This study on green skills and environmental awareness in VET identifies challenges, priorities and policy recommendations for taking advantage of the transition towards a green economy by facilitating labour-market responses to emerging skill needs. In particular, the study investigates the links between skill needs in the labour market and the responses of learning providers. This report claims that the main factors slowing down adaptation to the green economy and the development of necessary skills are the failure of employers to demand new qualifications, and the uncertainty surrounding regulations and policies. Learning providers also report difficulties in meeting the needs of employers and understanding what organisations' skill needs are. Overall, there is limited evidence that green policies have become part of the mainstream of skills development and hiring policies. There is clearly a potential for policy-makers and social partners to raise awareness and take common action." (Hrsg. , BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; G 2.3.4 Qualifikationswandel; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2 Europa; Berufsbildung; Nachhaltige Entwicklung; Umweltökonomie; Green skills / grüne Kompetenzen; Qualifikationswandel; Qualifikationsbedarf; Europa